Cloxacillin: A New Cause of Pill-Induced Esophagitis - Petros Zezos; Ziv Harel; Fred Saibil (Canadian Journal of Gastroenterology and Hepatology)
A large variety of medications can cause pill-induced esophagitis. Herein we present a case of cloxacillin-induced esophagitis. A 66-year-old male presented with an acute onset of epigastric and retrosternal pain on the 5th day of a course of oral cloxacillin prescribed for erysipelas. Initial clinical and imaging assessment was negative and he was sent home. A few days later, he returned with persistent severe retrosternal pain; endoscopy at the same day revealed a normal upper esophagus, several small stellate erosions in the midesophagus, and a normal squamocolumnar junction with a small hiatus hernia. Treatment with esomeprazole 40 mg bid and MucaineR suspension resulted in complete resolution of his symptoms. Pill-induced esophagitis may be underreported by patients, when symptoms are mild and unrecognized and/or underdiagnosed by the clinicians as a cause of retrosternal pain, odynophagia, or dysphagia. Failure of early recognition may result in unnecessary diagnostic investigations and prolongation of the patient’s discomfort. This case signifies the importance of enhancing clinician awareness for drug-associated esophageal injury when assessing patients with retrosternal pain, as well as the value of prophylaxis against this unpleasant condition by universally recommending drinking enough water in an upright position during ingestion of any oral medication.